Гормональные нарушения и патогенез рака яичник - Дудниченко, А.С.; Павлова, Т.Д.; Карташов, С.М.; Князева, М.В. (Онкологія, 2001)
Проанализированы данные литературы о гормональной зависимости рака яичника и о механизме участия эстрогенов в злокачественной трансформации. Исследованы уровни фолликулостимулирующего гормона, лютеинизирующего гормона, эстрадиола, прогестерона у пациенток с доброкачественными и злокачественными опухолями яичника. Literature data was studied concerning the pathogenesis of ovarian cancer with respect to hormonal dependence. The problem of estrogen-induced carcinogenesis was investigated with consideration for data related to the mechanism of estrogens’ effect on the malignant process of target cell transformation. The levels of folliclestimulating hormone, luteinizing hormone, estradiol, and progesterone were measured in patients with malignant and benign ovarian tumors.